2021
DOI: 10.1177/10870547211068039
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Diabetes Related Complications in Adults with Type 1 Diabetes Mellitus and ADHD

Abstract: Objective: To assess the correlation of co-morbid ADHD and diabetes-related complications in patients with type-1-diabetes-mellitus (T1DM). Methods: A retrospective cross-sectional study was conducted during 2018 using the Leumit-Health-Services(LHS) database. Diabetes-related complications were assessed in patients with T1DM and ADHD (T1DM-ADHD+) and compared with patients with T1DM alone (T1DM-ADHD−). Results: Out of 789 adult-patients with T1DM, 75 (9.5%) were T1DM-ADHD+, matched to 225 T1DM-ADHD−. HbA1C le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…In contrast with our findings, several previous studies have shown that the co-occurrence of ADHD in people with diabetes is associated with a greater rate of diabetes complications including, chronic renal failure [18] , [22] , [33] . A number of papers have reported that the dual diagnosis of ADHD and type 1 diabetes is associated with higher levels of blood glucose, HbA1c, higher systolic blood pressure and an increased number of diabetes-related complications including nephropathy [18] , [19] , [22] . The relatively few individuals in our study with advanced renal disease limited our ability to examine this association.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with our findings, several previous studies have shown that the co-occurrence of ADHD in people with diabetes is associated with a greater rate of diabetes complications including, chronic renal failure [18] , [22] , [33] . A number of papers have reported that the dual diagnosis of ADHD and type 1 diabetes is associated with higher levels of blood glucose, HbA1c, higher systolic blood pressure and an increased number of diabetes-related complications including nephropathy [18] , [19] , [22] . The relatively few individuals in our study with advanced renal disease limited our ability to examine this association.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown that adults with T2D and ADHD have significantly higher levels of fasting blood glucose (FBG), postprandial blood glucose (PBG), hemoglobin A1C (HbA1c), and required insulin dose/kg than those without ADHD [18] , [19] , [20] , [21] . It has also been reported that diagnosis of ADHD in adults with T2D is associated with an increased risk of diabetes-related complications such as neuropathy, ulcers, limb amputation, albuminuria, chronic renal failure, diabetic ketoacidosis, and elevated systolic blood pressure [18] , [19] . Adults with T2D and ADHD have also been found to have more emergency room admissions, greater annual hospitalization rates, longer hospital stays, and higher annual health spending costs in comparison to those without ADHD [18] , [22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, this is the first large-scale population-based epidemiological study to evaluate the association between G6PD deficiency and ADHD. This finding is in line with the association between ADHD and inflammatory somatic conditions [36][37][38], between ADHD and infectious diseases [25][26][27] and between G6PD deficiency and COVID-19 infection and immune-related diseases [39]. G6PD-deficient patients, similar to individuals with ADHD, exhibit a higher incidence of infectious diseases worldwide, indicating a vulnerability to infections [40,41].…”
Section: Discussionsupporting
confidence: 78%
“…For instance, clinical practices showed that antidepressant treatment could improve glycemic control in those with either depressive symptoms or depression . A recent cross-sectional study also found that among adults with comorbid T1D and ADHD, those taking ADHD medication had better diabetes outcomes than those with untreated ADHD. On the other hand, the metabolic effects of psychotropic medications, especially antipsychotics and mood stabilizers, have been of concern in deteriorating the metabolic profile of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%